2015
DOI: 10.1111/1540-6229.12089
|View full text |Cite
|
Sign up to set email alerts
|

Foreclosure Discount: Definition and Dynamic Patterns

Abstract: The lack of a consistent definition of foreclosure discount gives rise to discount rates that vary from nonexistent to sizeable across locations and time. We define the foreclosure discount as the discount of the real estate owned (REO) sale price relative to a normal‐sale estimated market value. With a dataset of 1.34 million REO sale transactions, across 16 CBSAs between 2000 and 2012, we find three noteworthy empirical findings. First, a high REO sale concentration in a market increases the foreclosure disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…As liquidity and price changes often follow each other, with higher liquidity and closer bid-ask spreads during up markets as compared to down markets, this is closely related to liquidity. Given that this found, the results are concurrent with earlier research on foreclosure discounts, having found that neighborhood value appreciation decreases the discount on price (Zhou et al, 2015). This does however contradict studies on the price-TOM relationship that have found a greater positive impact of TOM during periods of increasing property values (An et al,2013), as a greater positive impact of marketing time should correspond to a larger negative impact caused by a forced sale.…”
Section: Studies On the Impact Of Time And Marketing On Real Estate Ssupporting
confidence: 79%
See 4 more Smart Citations
“…As liquidity and price changes often follow each other, with higher liquidity and closer bid-ask spreads during up markets as compared to down markets, this is closely related to liquidity. Given that this found, the results are concurrent with earlier research on foreclosure discounts, having found that neighborhood value appreciation decreases the discount on price (Zhou et al, 2015). This does however contradict studies on the price-TOM relationship that have found a greater positive impact of TOM during periods of increasing property values (An et al,2013), as a greater positive impact of marketing time should correspond to a larger negative impact caused by a forced sale.…”
Section: Studies On the Impact Of Time And Marketing On Real Estate Ssupporting
confidence: 79%
“…The expected effect is that higher priced neighborhoods should be associated with lower discounts, i.e. having a positive coefficient, as this is supported by previous research such as Campbell et al (2011) and Zhou et al (2015). Earlier studies have related this combination to seller costs of protection.…”
Section: Estimation Using Appraisal Valuessupporting
confidence: 52%
See 3 more Smart Citations